2021
DOI: 10.3390/diagnostics11040728
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Withdrawal—An Overview on When and How to Diagnose Adrenal Insufficiency in Clinical Practice

Abstract: Glucocorticoids (GCs) are widely used due to their anti-inflammatory and immunosuppressive effects. As many as 1–3% of the population are currently on GC treatment. Prolonged therapy with GCs is associated with an increased risk of GC-induced adrenal insufficiency (AI). AI is a rare and often underdiagnosed clinical condition characterized by deficient GC production by the adrenal cortex. AI can be life-threatening; therefore, it is essential to know how to diagnose and treat this disorder. Not only oral but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 64 publications
0
16
0
1
Order By: Relevance
“… 37 , 38 The diagnosis of such infraclinical adrenal insufficiency might be very difficult to detect. 39 It can therefore not be excluded in those patients with CSCR who have been treated even several months or years ago with glucocorticoids and might present with relative adrenal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“… 37 , 38 The diagnosis of such infraclinical adrenal insufficiency might be very difficult to detect. 39 It can therefore not be excluded in those patients with CSCR who have been treated even several months or years ago with glucocorticoids and might present with relative adrenal insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Furthermore, it has been demonstrated that 68% of patients with AI had an incorrect diagnosis at first. [24] However, in none of the studies, information was available on the physicians' education, knowledge on GC replacement, or medical specialty. The findings of the present study and the two previous studies [9,10] fill this gap in various professional groups and support the idea to provide ongoing education to physicians on AI, a rare but essential disorder since patients rely in large parts on the information provided by their physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Рекомендуется заменить обычно применяющиеся препараты средней длительности действия (преднизолон, метилпреднизолон) на гидрокортизон для приема внутрь (2 или 3 приема в день) [12,13]. По мнению эндокринологов, относительно короткое действие гидрокортизона способствует восстановлению функции оси гипоталамусгипофиз-надпочечники в промежутках между приемами препарата [14]. Суточная доза гидрокортизона устанавливается индивидуально и с учетом той дозы ГК, которая применялась в период исследования уровня кортизола в крови.…”
Section: псевдообострения ревматической полимиалгииunclassified